2020
DOI: 10.1039/c9ay01887e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of tetracycline in honey by microwave plasma torch mass spectrometry with ablation samples

Abstract: A rapid and sensitive mass spectrometric analysis method with minimal or no prior sample pretreatment was developed for the direct detection of trace amounts of tetracycline in honey products using a microwave plasma torch combined with mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In an early work, Gray M. Hieftje et al built an MPT-TOF MS for the detection of halogenated hydrocarbons separated by a capillary gas chromatography [ 131 ]. After a long time, Ti-Qiang Zhang as well as Zhi-Qiang Zhu [ 22 , 23 , 132 ] studied the direct desorption/ionization approach of MPT on a linear ion trap (LTQ) mass spectrometer to analyze a series of small organic molecules, and they showed that MPT is a useful alternative ambient ion source. Zhi-Qiang Zhu’s group [ 24 , 25 , 26 , 133 , 134 , 135 , 136 ] has also completed a lot of work on the detection of trace metal in aqueous solutions by MPT source, coupled with a mass spectrometer (MPT-MS), reaching an in-depth understanding of the characteristics of MPT.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In an early work, Gray M. Hieftje et al built an MPT-TOF MS for the detection of halogenated hydrocarbons separated by a capillary gas chromatography [ 131 ]. After a long time, Ti-Qiang Zhang as well as Zhi-Qiang Zhu [ 22 , 23 , 132 ] studied the direct desorption/ionization approach of MPT on a linear ion trap (LTQ) mass spectrometer to analyze a series of small organic molecules, and they showed that MPT is a useful alternative ambient ion source. Zhi-Qiang Zhu’s group [ 24 , 25 , 26 , 133 , 134 , 135 , 136 ] has also completed a lot of work on the detection of trace metal in aqueous solutions by MPT source, coupled with a mass spectrometer (MPT-MS), reaching an in-depth understanding of the characteristics of MPT.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…After starting with a brief review on the hazards, migration, distribution and traditional analysis methods of PAHs which are widely used in recent years, including liquid chromatography, gas chromatography and surface enhanced Raman spectroscopy and so on, we mainly want to present the applications of the modern ambient mass spectrometry in the detection of PAHs; in addition, we present the far out novel results in our lab by using microwave plasma torch (MPT) mass spectrometry, which exhibited the versatility of MPT MS as a platform in the research of PAHs. MPT ion source is a novel ambient ion generator and has multiple advantages, for example, simple construction of the device and easy operation, low power dissipation, relative high sensitivity, and suitable for many types of samples including metal elements and organic samples [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the MPT has shown excellent performance as an atmospheric pressure ion source for the analysis of organic and metallic elements. 28,29 In this work, we combined MPT and corona discharge as dual sources to enhance ionization efficiency and applied it to the analysis of sterols in urban water systems using Orbitrap MS. Preliminary results show that the dual source can be directly used for sterol detection, and four target sterols were detected in water samples collected from different areas of Hangzhou city.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave plasma torch (MPT) ion source was developed by Jilin University, China, in 1985 and has been used as an excitation light source in AES. In the last decade, the MPT has shown excellent performance as an atmospheric pressure ion source for the analysis of organic and metallic elements 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…Much research has been done on various ionization techniques optimizing performance for specific analyses. , The flexibility afforded by changing many physical or chemical parameters while performing ambient ionization has given practitioners many options to tailor the ion source to maximize performance. Examples of ionization methods for the antibiotic detection in complex matrixes include the following: electrospray ionization (ESI) for milk samples, nano-electrospray ionization (nESI) for infant formula, paper spray for biofluids, microwave plasma torch (MPT) for honey, and extractive electrospray ionization (EESI) for viscous cosmetic products, with sample preconcentration and cleanup methods, such as solid-phase microextraction (SPME), ,, solid-phase extraction (SPE), or simplified extraction often being necessary to compensate for the lack of chromatographic separation. Requiring minimal sample preparation and time, ambient ionization is most impactful when coupled to mass spectrometers that can be operated outside an analytical laboratory.…”
Section: Introductionmentioning
confidence: 99%